2023
DOI: 10.1007/s40544-023-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact-sliding fretting tribocorrosion behavior of 316L stainless steel in solution with different halide concentrations

Abstract: Impact–sliding caused by random vibrations between tubes and supports can affect the operation of heat exchangers. In addition, a corrosive environment can cause damage, accelerating the synergism of corrosion and wear. Therefore, the focus of this work was the impact–sliding fretting tribocorrosion behavior of 316L heat exchanger tubes at different halide concentrations. A device system incorporating the in situ electrochemical measurements of impact–sliding fretting corrosion wear was constructed, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Before the fretting corrosion test, the OCP usually decreased with an increase in the salt spray duration [Figure 11(a)], indicating the increased corrosion sensitivity of the tube surface. An increase of the salt spray duration can increase the amount of Cl − ions adsorbed on the alloy surface, thereby affecting the integrity and stability of the passive film (Ma et al , 2023). The OCPs of all the treated samples were reduced after the fretting corrosion test [Figure 11(b)].…”
Section: Resultsmentioning
confidence: 99%
“…Before the fretting corrosion test, the OCP usually decreased with an increase in the salt spray duration [Figure 11(a)], indicating the increased corrosion sensitivity of the tube surface. An increase of the salt spray duration can increase the amount of Cl − ions adsorbed on the alloy surface, thereby affecting the integrity and stability of the passive film (Ma et al , 2023). The OCPs of all the treated samples were reduced after the fretting corrosion test [Figure 11(b)].…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al (2021) studied the wear of 316L stainless steel in solutions with five different SO 4 - /Cl - ratios (from 0.31 M: 0 to 0:0.62 M), and found that the synergistic effect between wear and corrosion was the main factor causing material loss. Ma et al (2023) studied the impact-sliding fretting corrosion behavior of 316L stainless steel in solution with different halide concentrations, and found that the lubricity and corrosivity of the solution, respectively, dominated different concentration ranges.…”
Section: Introductionmentioning
confidence: 99%